PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA DI SMA NEGERI 11 PEKANBARU - Lily Imelda S; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by environmental conditions and their influence on the character building of students. This research aims to : (1) To find out the school environment of senior high school 11 Pekanbaru. (2)To find out the character of students in senior high school 11 Pekanbaru. (3)To determine the effect of the school environment on character building for students of senior high school 11 Pekanbaru. Type of this research use quantitative research. The population in this study were all students of class X and X1 in senior high school 11 Pekanbaru as many as 264 students. The research sample was 94 students. The technique used in sampling is the Probability sampling technique. The technique of collecting data use online questionnaires through distributing questionnaires using Google Form. For the data questionnaire obtained using a Likert scale, which is a scale used to measure attitudes, which are arranged in the form of questions and followed by responses that indicate levels with alternative answers Always, Sometimes, Rarely, Never to measure variables X and Y. The data analysis technique that the researcher uses is simple linear regression. The research results from the tests, it is known that the school environment has a positive effect on the formation of student character, meaning that whenever there is an increase in the school environment, there will also be an increase in the formation of student character towards a better direction. This is reinforced and supported by the significance value smaller than the alpha value, namely 0.00 <0.05, meaning that the school environment of senior high school 11 Pekanbaru has a positive and significant effect on the character building of students at senior high school 11 Pekanbaru. Furthermore, it can be seen from the t count is greater than t table (7,265> 1,986 means that Ho is rejected and Ha is accepted. Thus, it shows that the school environment of senior high school 11 Pekanbaru has a positive and significant influence on the character building of students at senior high school 11 Pekanbaru.Key Words: Influence, School Environment, Character